ANALISIS FAKTOR PENENTU DALAM PENGELOLAAN BERKELANJUTAN ESTUARIA DAS TALLO - Muhammad Yusuf; Cecep Kusmana; Achmad Fahrudin; M Mukhlis Kamal (Jurnal Analisis Kebijakan Kehutanan, 2016)
Population growth will affect landuse changes drastically, particularly in watersheds (DAS) and coastal zone. Something similar happened to the Tallo watershed estuaries, Makassar Urban. This study aimed to (1) analyze the sustainable management of Tallo watershed estuaries, (2) driven factors analysis on sustainability of Tallo watershed estuaries, and (3) the alternative of policy development on sustainable management of Tallo watershed estuaries. MDS analysis with Rapest results showed the status of Tallo watershed estuaries were less sustainable (49.20%), consist of;  ecological dimension (46.51%), economic dimension (42.22%), social dimension (43.90%), technology dimension (45.99%), and institutional dimension (46.83%). The driven factors on sustainability management of Tallo watershed estuaries, consists of five (5) attributes i.e; institutional facilities property right population density, resource technology and aquaculture technology. The policy development direction on sustainable management of Tallo watershed estuaries, consist of; alternative I is strengthening institutional management, and the second alternative was using resources in the sustainable ways.